Penerapan Model Pembelajaran Project Based Learning Untuk Meningkatkan Hasil Belajar Matematika Siswa di Kelas 2 SD Inpres Anagowa Kabupaten Gowa - Sumiara, Sumiara; Yusuf, Faidah; Sukmawati, Andi (Universitas Negeri Makassar, 2025)
The aim of this research is to describe the steps for implementing the Project-Based Learning (PjBL) model to improve mathematics learning outcomes for class II students. This type of research is classroom action research (PTK) which is carried out in two cycles. This research was conducted at SD Inpres Ana Gowa, Gowa Regency with the research subjects being grade 2 students at SD Inpres Ana Gowa, totaling 23 subjects. The basic activities of the learning process carried out by teachers all apply the steps of the project-based learning model (PjBL), namely (a) identifying basic questions, (b) preparing a project design; (c) schedule setting; (d) integrating project progress; (e) assessment of results; f) evaluation of experience. The research results show an increase in learning outcomes through the application of the project-based learning model for grade 2 elementary school students. This is proven by the increase. Student learning outcomes also increased with the average student learning score in the initial condition being 11 students (75%), increasing in cycle 1 with the average student score being 72 with the number of students being 12 people (85%), and in cycle 2 it was obtained The average score was 89 students, with 23 students completing or (89%).